The Role of Technology Readiness in Islamic Financial Technology Acceptance Among MSMEs: An Empirical Integration Analysis TPB and TAM Framework - Muhammad Hanif Ibrahim; Fauziyah Fitri; Rasikh Saifan Ahmad (Department of Islamic Economics, IPB University, 2024)
Indonesia with the largest Muslim population in the world is expected to become the world's leading Islamic finance center. With a large Islamic economic base, Islamic FinTech has an important role in economic expansion in Indonesia. MSMEs as an instrument of economic growth in Indonesia, are expected to maximize the presence of Islamic financial technology for efficient and effective payments, expand market access, and facilitate access to finance and capital. On the other hand, the technology readiness of MSMEs is an important factor that needs to be investigated to see the acceptance of MSMEs towards the use of Islamic financial technology in Indonesia. This study analyzes the factors that influence MSMEs' intention to use Islamic FinTech services. This study involved 140 MSMEs from several regions in Indonesia as respondents. The analysis used partial least square structural equation modeling (SEM-PLS). By the objectives, four variables from TPB and TAM influence the intention to use Islamic financial technology, namely Islamic religiosity, ease of use, usefulness, and technology readiness. Finally, technology readiness is strongly correlated to the use of Islamic financial technology. The results of this study provide a comprehensive perspective for policymakers to improve the quality of applications so that it will also increase the intention of MSMEs to adopt Islamic FinTech. The results of this study can also be input, especially for the Financial Services Authority (OJK) to be able to promote Islamic FinTech and coordinate with Islamic FinTech to be able to provide the best service to users.